Antibacterial effects of Brazilian and Bulgarian propolis and synergistic effects with antibiotics acting on the bacterial DNA and folic acid - Orsi, Ricardo de Oliveira [UNESP]; Fernandes, A. [UNESP]; Bankova, V.; Sforcin, J. M. [UNESP] (Taylor & Francis Ltd, 2012)
Propolis is a honeybee product that has been used since ancient times because of its therapeutic effects. It can be used in the development of alternative therapies for the treatment of many diseases, and because propolis shows antibacterial action, this work was carried out in order to investigate a possible synergism between propolis and antibiotics acting on DNA (ciprofloxacin and norfloxacin) and on the metabolism (cotrimoxazole) against Salmonella Typhi. Propolis samples collected in Brazil and Bulgaria were compared in these assays, and the synergism was investigated by using 1/2 and 1/4 of the minimal inhibitory concentration for propolis and antibiotics, evaluating the number of viable cells according to the incubation time. Brazilian and Bulgarian propolis showed antibacterial activity, but no synergistic effects with the three tested antibiotics were seen. Previous works by our laboratory have revealed that propolis has synergistic effects with antibiotics, acting on the bacterial wall and ribosome, but it does not seem to interact with antibiotics acting on DNA or folic acid, and only a bacteriostatic action was seen in these assay conditions.
Keywords: propolis; antimicrobial activity; synergistic effects